Financial Altruism is Associated with Alzheimer's Disease Neurocognitive Profile in Older Adults. (20th December 2022) - Weissberger, Gali H; Samek, Anya; Mosqueda, Laura; Nguyen, Annie; Lim, Aaron; Fenton, Laura E.; Han, Duke
Abstract: Background: Older age is associated with an increase in altruistic behaviors such as charitable giving. The present study aimed to investigate the cognitive correlates of financial altruism in older adults. Method: Older adults ( N  = 67; M age = 69.21, SD = 11.23; M education years = 15.97, SD  = 2.51; 58.2% female; 71.6% Non‐Hispanic White) completed a comprehensive neuropsychological assessment and an altruistic choice paradigm in which they made decisions about allocating money between themselves and an anonymous person. Result: In multiple linear regression analyses that controlled for age, education, and sex, financial altruism was negatively associated with performance on cognitive measures typically sensitive to early Alzheimer's Disease (including word list learning and recall, delayed story recall, and animal fluency). When financial altruism responses were grouped, differences between altruistic groups revealed that individuals who gave more than they kept for themselves demonstrated the worst cognitive performance compared to those who gave equally (kept half and gave half) and those who gave less (kept more and gave less). Conclusion: Findings of this study point to a negative relationship between financial altruism and cognitive functioning in older adults on measures known to be sensitive to Alzheimer's Disease (AD). Findings also point to a potential link between financial exploitation risk and AD in older age.